(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
Pushkin! This sunny name accompanies us all our lives. We hear it for the first time in early childhood and, not yet able to read, we already repeat by heart from the words of our mother: "The wind walks on the sea and the boat urges."